2010
DOI: 10.1111/j.1600-0404.2010.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise alleviates debilities of normal aging and Alzheimer’s disease

Abstract: Both healthy aging and the pathologic incidence of disorders associated with aging involve an array of debilities. Physical exercise harnesses implicit and inherent biologic characteristics amenable to the putative interventional influences under clinical, institutional or laboratory conditions. The neurodegenerative and pathophysiologic progressions that constitute Alzheimer's disease (AD), amnestic mild cognitive impairment (aMCI), normal aging, and different animal models of AD have shown the existence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 303 publications
(297 reference statements)
4
61
0
5
Order By: Relevance
“…Many epidemiological studies, intervention trials, and animal experiments have demonstrated that memory dysfunction, which is the predominant symptom of dementia and Alzheimer's disease, can be prevented and reduced in aged subjects through physical exercise [20][21][22]. However, the effects of physical exercise on mental concentration in the elderly are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many epidemiological studies, intervention trials, and animal experiments have demonstrated that memory dysfunction, which is the predominant symptom of dementia and Alzheimer's disease, can be prevented and reduced in aged subjects through physical exercise [20][21][22]. However, the effects of physical exercise on mental concentration in the elderly are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there has been little information available about the effect of physical exercise on the levels of mental concentration in elderly people, whereas many reports state that physical exercise can prevent and improve memory impairment in adult humans [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies have indicated that activity and active engagement in daily activities bolsters neurocognitive functioning [39]. As implied by Mattson [40] and others [41][42][43][44][45][46], HAND patients ought to benefit from the plethora of health advantages bestowed by regular physical exercise: accelerated brain-derived factor and other trophic factor production, enhanced synaptic (even axonal) plasticity, neurogenesis and neuron arborization, increased production of anti-inflammatory cytokines and other aspects of improved neuroimmune functioning, and marked dividends for cognitive performance and affective balance. Furthermore, exercise intervention was applied to fifteen HIV-infected individuals between 35 and 51 years-of-age, and improvements in hand strength, scapular force, and several quality-of-life domains, including environment, perception of quality-of-life and global health [47,48].…”
mentioning
confidence: 98%
“…Severe, selective cortical atrophy in regions of the brain such as the temporal, medial temporal, limbic, frontal, and prefrontal cortices is one of the hallmarks of neurodegenerative and age-related dementia [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The functional and cognitive attributes affected by the deterioration of these brain structures include learning, memory, attention, motivation, executive function, motor function, global cognition, and activities during daily living [5,7]. MCI, which is often a prelude to dementia [8,9], is also associated with disproportionate atrophy in the medial temporal and temporal cortices [6,7].…”
Section: Introductionmentioning
confidence: 99%